ANALISIS FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI EKONOMI RUMAHTANGGA PETANI PADI SAWAH DI KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR - Marissa Chintia; Syaiful Hadi; Djaimi Bakce (Jurnal Ilmiah Pertanian, 2017)
The purpose of this study was to analyze the factors that influence the economic decisions of the household paddy farmer associated with the production, allocation of working time, income, and expenditure. To answer the purpose of research conducted by econometric approach using a model of simultaneous equations with the method Two Stage Least Square (2SLS). The data used is the 2016 cross section data which obtained by interviewed 45 paddy farmers in the district of Batang Tuaka. The result showed:Firstly, the dominant factor affected production is harvested area. Secondly, the dominant factors affected allocation of working time are income of farming, allocation of working outside the farming, labor force, age of farmers, the experience of farmers, allocation of working time on farming, farmers education, and the other income of farming.Thirdly, the dominant factors affected other income of farming are allocation of working outside the farming, age of farmers, farmers wife education, and labor force. Fourthly, the dominant factors affected expenditure are household total income, family member, health expenditure, number of children school, harvested area, food consumption, household total expenditure, education invesments, and savings.Policy implications that can be taken by the government to develop paddy farming to increase the production of dried paddy in the district of Batang Tuaka is with the improvement and development of infrastructure and facilities of agriculture. The increase in production to push income needs supported by the pricing of dried paddy pro farmers and stabilize the prices of inputs.